Carbazole-based compounds as photoinitiators for free radical and cationic polymerization upon near visible light illumination. Issue 5 (5th April 2018) - Al Mousawi, Assi; Arar, Ahmad; Ibrahim-Ouali, Malika; Duval, Sylvain; Dumur, Frédéric; Garra, Patxi; Toufaily, Joumana; Hamieh, Tayssir; Graff, Bernadette; Gigmes, Didier; Fouassier, Jean-Pierre; Lalevée, Jacques
Abstract : Six new carbazole based compounds are synthesized and proposed as high performance photoinitiators for both the free radical polymerization of acrylates and the cationic polymerization of epoxides. Abstract : Six new carbazole based compounds (Ca1–Ca6) are synthesized and proposed as high performance photoinitiators with iodonium salt (iod) and/or an amine (EDB) for both the free radical polymerization (FRP) of acrylates and the cationic polymerization (CP) of epoxides upon near UV and visible light exposure using light emitting diodes (LEDs) @385 nm and @405 nm. Excellent polymerization initiating abilities are found and high final reactive function conversions are acquired. A full picture of the involved photochemical mechanisms is given.